Hubungan Antara Harapan Mempertahankan Hubungan Terhadap Kecenderungan Toxic Relationship Pada Wanita Yang Pacaran - Syamsidar HR; Eva Meizara Puspita Dewi; Haerani Nur (Arden Jaya Publisher, 2023)
Early adulthood is generally the stage of starting to like the opposite sex and committing to marriage. The desire to form a relationship with the opposite sex takes place with a relationship called dating. However, in the process of dating, things often happen that make couples uncomfortable with their partners and interfere or are often called toxic relationships. This study aims to determine the relationship between the hope of maintaining a relationship and the tendency of toxic relationships in women who are dating. The participants in this study were 461 women aged 18-25 years. The measuring instruments used in this study are adult hope scale and toxic relationship scale. The data analysis used in this study is spearman rank correlation which is processed using SPSS 24.0 for windows. The results of this study indicate that there is a significant relationship between the hope of maintaining a relationship and the tendency of toxic relationships in women who are dating. The significance value (p = 0.000) and the Spearman rank correlation (r = -0.494) indicate that there is a negative relationship between the variable hope of maintaining the relationship and the tendency of toxic relationships in women who are dating. This means that women who have high hopes of maintaining a relationship have a low level of toxic relationship tendencies when dating. Vice versa, if the hope of maintaining the relationship is low, the tendency of toxic relationships when dating is high. The implication in this study is to recommend to women aged 18-25 years, especially those who are in a dating relationship in order to avoid toxic relationships.